Research on the operation mechanism of "three complete education" in Chinese universities in the new Era - Zhang, Zhenwu; Zheng, Zhihui (Journal of Roi Kaensarn Academi, 2024)
Since the 18th National Congress of the Communist Party of China, the construction of socialism with Chinese characteristics into a new era, in the face of new challenges new requirements, China’s higher education attaches great importance to ideological and political education, put forward and constantly improve the "three complete education" ideological and political education work mechanism, realize the full education, education, all-round education. This study analyzes the research of "three complete education" in Chinese universities in the new era from a holistic perspective, introduces the research background, and summarizes the research status of "three complete education" at home and abroad. Carry out theoretical analysis, define the concept of "three complete education", sort out the historical development context of "three complete education", divide it into four stages of proposal, exploration, formation and rise, and summarize the theoretical origin and theoretical basis of "three complete education". To carry out empirical research, five Chinese universities were selected as samples to conduct questionnaire survey and analysis, and found the main problems in the operation process of the "three complete education" mechanism in Chinese universities. Finally, the countermeasures to promote the benign operation of the "three whole education" mechanism are put forward: the second is to achieve the unity of opposites between the whole and part in the reform of ideological and political education, and the unity of opposites and innovation in the process of strengthening the effectiveness of ideological and political education.